Reparação óssea em alvéolos de ratas ovarectomizadas após implante com biovidro: análise histomorfométrica e imunoistoquímica - Azenha, Marcelo Rodrigues [UNESP] (2013)
Objectives: To evaluate the process of alveolar repair in ovariectomized rats after implantation with Biosilicate. Materials and Methods: Sixty rats were divided into four groups (n = 15) according to treatment: Group 1 - rats underwent sham surgery with alveoli filled with blood clot; Group 2 - rats underwent sham surgery with alveoli filled with crystalline Biosilicate; Group 3 - ovariectomized rats with alveoli filled with blood clot; Group 4 - ovariectomized rats with alveoli filled with crystalline Biosilicate. After 7, 14 and 28 days the animals were sacrificed and histomorphometric analysis (histology and histometric) and immunohistochemical (Osteopontin and Osteocalcin) were measured . The comparison of the results was performed using the statistical program Assistat 2013 for Windows by Analysis of Variance and Mann-Whitney tests, with significant results being found when p ≤ 0:05 . Results: During the 7- day period, Groups 1 and 3 showed better and significantly higher results in bone formation than Groups 2 and 4 (p<0.05). After 14 days the statistical differences remained between Groups 1 and 3 and Groups 2 and 4 (p<0,05). At 28 days, the statically difference remained significant between the same Groups, while the groups implanted with Biosilicate presented about 60% of the socket filled by new bone. Immunohistochemistry revealed expression of proteins osteocalcin and osteopontin, especially in animals subjected to ovariectomy surgery. Conclusions: Groups 1 and 3 were those with the best results throughout the study, with the crystalline Biosilicate presenting favorable result in bone repair without bioglass resorption. The immunohistochemical analysis showed that animals subjected to ovariectomy had a higher signaling in Ostecalcina and Osteopontin proteins